The Determinants of Bank’s Liquidity: Comparative Analysis From Global Islamic Banks and Conventional Banks - Jaafar, Mohamad Nizam; Mohammad Hatta, Mohammad Firdaus; Muhamat, Amirul Afif; Abdul Karim, Norzita; binti Mohd Idris, Ummul Athirah Fathihah; binti Mohamad Zamri, Nur Qurratuain Mardhiah (Information Management and Business Review, 2024)
This study investigates the determinants of bank liquidity in both Islamic and Conventional banks across 15 countries, focusing on key variables such as profitability, capital adequacy, bank size, and credit risk. Utilizing data from 107 Islamic banks and 506 Conventional banks spanning from 2013 to 2022, the analysis reveals significant differences in liquidity management between the two banking systems. The Random Effect Model (REM) was employed based on the Hausman test results to ensure robustness. The findings indicate that profitability negatively impacts liquidity in Islamic banks, likely due to investments in less liquid, Sharia-compliant assets, while it positively influences liquidity in Conventional banks, where profits are often reinvested into liquid assets. Capital adequacy emerges as a crucial determinant of liquidity in both bank types, highlighting the importance of maintaining strong capital buffers. The study also finds that credit risk significantly reduces liquidity in Conventional banks, whereas it has a lesser impact on Islamic banks. These insights contribute to a deeper understanding of liquidity management practices in Islamic and Conventional banks, offering valuable implications for bank managers, policymakers, and regulators.